Sidik Jari Sebagai Pendukung Pembuktian Pembunuhan (Studi di Polres Mataram) - Erich Mahesa; Idi Amin (PT Satya Pertama Nusantara, 2023)
The purpose of this study is to find out and understand the function and strength of fingerprints as support in proving the crime of murder, and find out the effectiveness of fingerprints as supporting evidence for proving the crime of murder at the Mataram Police. This research uses the empirical legal research method, the data sources obtained from this research come from observations and interviews, and data analysis is used through qualitative analysis methods with descriptive analysis. The criminal acts regulated in Article 338 of the Criminal Code are the primary criminal acts, namely criminal acts that have been formulated in full with all their act elements. In the investigation process, finding the truth about the criminal act is not easy because there is often a lack of evidence and witnesses. So that investigators have to work harder in gathering valid evidence to get to the truth. The legal status of fingerprint proof as evidence in criminal cases, namely as evidence of expert testimony, letters, and instructions, is strong and valid, based on Article 184 of the Criminal Procedure Code.